Designing a SMART algorithm-based decision support system for streamlining makeup selection through prototyping development - Wazaumi, Dwi Diana; Wardani, Deyana Kusuma; Abdullah, Abdul Aziz (Jurnal Info Sains : Informatika dan Sains, 2024)
The research on developing a cosmetic makeup product recommendation system emerged in response to various common skin issues resulting from improper makeup usage, especially among teenagers. This study emphasizes the utilization of the Simple Multi-Attribute Rating Technique, considering criteria such as skin type, skin problems, age, price, shade, and longevity of the product. However, in testing 8 scenarios, the obtained accuracy was 62%, possibly due to the limited variations of alternatives tested. The hope is that this recommendation system can serve as a solution for the public in selecting cosmetic products that better suit their individual skin conditions, consequently aiding in reducing common skin problems resulting from inadequate product choices.